New and little known corophiidean amphipods from the 'Lucky Strike' hydrothermal vent, Mid-Atlantic Ridge - Myers, Alan A. (2013)
Two species of corophiid amphipods are described from the `Lucky Strike' hydrothermal vent on the Mid-Atlantic Ridge near the Acores. One species, Bonnierella compar sp. nov is new to science, the other, Autonoe longicornis has not been reported since the original description of a single female in 1909. Full descriptions are provided of the new species, and of the previously unknown male of A. longicornis.